Cross-Linguistic Analysis of Latin-Derived Terms: Implications for Language Policy in Multilingual Societies - Nagima, Ilyassova; Saule, Asanbayeva; Aisulu, Nurtayeva; Dana, Pashan; Mukhtar Үеshimov (Journal of Ecohumanism, 2024)
This study investigates the influence of Latin-origin words in the Kazakh and English languages, focusing on terms related to "experience" and "problems." The research analyzes the etymology, modern usage, and challenges arising from the incorporation of these terms into Kazakh, a non-Latin script language. The study highlights the role of Latin-derived vocabulary in modern scientific, technological, and academic discourse, and the unique linguistic and cultural challenges it presents in Kazakh. A comparative analysis of the Kazakh and English terms for "experience" and "problems" is provided, emphasizing the nuances of meaning, connotation, and cultural differences in their use. The study also discusses the tension between modernization and linguistic purity in Kazakh, considering the impact of globalization on native language development. The relevance of this research lies in the growing significance of Latin-derived terminology in non-Latin script languages, particularly in the context of globalization. The study explores how Latin-origin words are both shaped by and reshape the cultural and linguistic landscape in Kazakh and English, contributing to the ongoing discourse on language standardization, bilingual education, and cultural preservation in the face of globalization. The findings underscore the complex interplay of language, culture, and global interconnectedness, presenting implications for future linguistic policy and language planning, especially within multilingual societies.